The enteric microbiota regulates jejunal Paneth cell number and function without impacting intestinal stem cells. (2nd January 2019) - Schoenborn, Alexi A.; von Furstenberg, Richard J.; Valsaraj, Smrithi; Hussain, Farah S.; Stein, Molly; Shanahan, Michael T.; Henning, Susan J.; Gulati, Ajay S.
ABSTRACT: Paneth cells (PCs) are epithelial cells found in the small intestine, next to intestinal stem cells (ISCs) at the base of the crypts. PCs secrete antimicrobial peptides (AMPs) that regulate the commensal gut microbiota. In contrast, little is known regarding how the enteric microbiota reciprocally influences PC function. In this study, we sought to characterize the impact of the enteric microbiota on PC biology in the mouse small intestine. This was done by first enumerating jejunal PCs in germ-free (GF) versus conventionally raised (CR) mice. We next evaluated the possible functional consequences of altered PC biology in these experimental groups by assessing epithelial proliferation, ISC numbers, and the production of AMPs. We found that PC numbers were significantly increased in CR versus GF mice; however, there were no differences in ISC numbers or cycling activity between groups. Of the AMPs assessed, only Reg3γ transcript expression was significantly increased in CR mice. Intriguingly, this increase was abrogated in cultured CR versus GF enteroids, and could not be re-induced with various bacterial ligands. Our findings demonstrate the enteric microbiota regulates PC function by increasing PC numbers and inducing Reg3γ expression, though the latter effect may not involve direct interactions between bacteria and the intestinal epithelium. In contrast, the enteric microbiota does not appear to regulate jejunal ISC census and proliferation. These are critical findings for investigators using GF mice and the enteroid system to study PC and ISC biology.